Efficacy of the elementary, middle, and high school students’ persuasive speech: Evidence from South Korea - Yune Jung Kim; Inhye Heo (International Journal of Evaluation and Research in Education (IJERE), 2023)
This paper aims to analyze the efficacy of elementary, middle, and high school students with respect to using persuasive speech and establish a direction for the development of relevant education. It examines the case of South Korea, where the government has presented the importance of persuasive speech education and implemented considerable measures since 2015. It utilizes the survey results on the perception around persuasive speech, based on the achievement standard set within the Korean language curriculum for elementary, middle, and high school students. The research offers several recommendations. First, it is necessary to specify educational content so that it applies differentially, according to the conditions of students. Second, educational content that addresses students’ attitudes, self-awareness, and participation in community issues must be reinforced. Third, educational content related to persuasion preparation, content organization methods, strategies, and meta-cognitive aspects must be presented sequentially in terms of beginning, development, and application, as suited to each level of education. Fourth, it is necessary to review the teaching-learning methods to increase the effectiveness of persuasive speech education. Fifth, it is necessary to especially consider the disadvantages of middle school students, who have huge gaps in efficacy with respect to their knowledge of persuasive speech.